Volatile Temperatures and Their Effects on Equity Returns and Firm Performance - Leonardo Bortolan; Atreya Dey; Luca Taschini (CESifo GmbH, 2024)
We establish the financial materiality of temperature variability by demonstrating its impact on US firms and investors. A long-short strategy that sorts firms based on exposure earns a market-adjusted alpha of 39 basis points per month. This variability metric is related to aggregate decreases in firm profitability, with asymmetric effects across industries. These outcomes are driven by reductions in consumer demand and labor productivity coupled with changes in media and investor attention. The geographically scalable statistical framework provides a reference for assessing the quantitative effects of climate-related physical risks, offering a metric for improving the disclosure of material climate risks.
Keywords: C21; C23; G12; G32; Q54; 330; corporate climate reporting; climate attention; temperature variability; stock returns; firm performance